ANALISIS FRAUD DIAMOND DALAM MENDETEKSI POTENSI FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN LQ-45 PERIODE 2011-2016 - Nadia Adelina; Senny Harindahyani (CALYPTRA, 2018)
The purpose of this research is to analyzes the variables that influence the occurence of financial statement fraud using fruad diamond, those are; Pressure can be seen from the financial stability, external pressure, and financial targets. Then, opportunities can be seen from the Big 4. Meanwhile, for rationalization can be seen from turn of auditor and audit opinion. And the last one is the capability can be seen form turn of director. The sample of this research using 15 companies which are always listed on the LQ-45 index in Indonesia Stock Exchange Effect from 2011-2016. The test equipment data using SPSS 20 includes descriptive statistical analysis, classic assumption test, the coefficient of determination test, simultaneous significant test, and hypothesis test. The results of this study showed that the variable external pressure and turn of director proven significant positive effect and variable financial stability, financial target, big 4, turn of director and opinion auditor are not proven on the fraud on financial report. The result of this research hoped to be a reference for future research and other users of financial information in detecting fraudulent of financial report.